Designing sustainability changes in a tourist accommodation context from a systems perspective - Coghlan, Alexandra; Becken, Susanne; MacAskill, Stefen (Frontiers in Sustainable Tourism, 2023)
Pro-sustainability changes are slow and incremental at best in the tourism sector. Research on the topic can take the form of secondary data (e.g. content analysis of strategic documents, social media posts), survey-based intent studies (e.g. willingness to pay), survey-based studies of self-reported behaviours, observation of actual behaviours (e.g. benchmarking studies), lab-based experimental manipulations of measurable behaviours, and finally in-situ, or field-based, experimental manipulations of measurable behaviours. The latter are some of the rarest studies and are held up as the gold standard for changing behaviours by providing evidence-based, measurable, actionable sustainability interventions for tourism businesses. This study draws inspiration from a four-year program of action research into pro-sustainability changes in tourist accommodation. It questions whether any of these approaches are sufficient for changing sustainability-oriented behaviours. This questioning extends to whether the theoretical approaches that underpin even "gold standard experiments" capture the operational contexts of accommodation businesses. It proposes instead that a scaffolded approach, built from a systems map of the theories, tools, experimental findings, interviews with stakeholders and operational context is necessary to create sustainability transformations in tourism businesses. This is a radical departure from the dependent/independent variable approach adopted in traditional scientific methods and requires a different ontological approach to the science of sustainability. The study has implications for contextualising intervention-based experimental studies within a wider system of influential factors within tourist accommodation.